2013
DOI: 10.1136/bjsports-2012-092101.15
|View full text |Cite
|
Sign up to set email alerts
|

Sport concussion knowledge base, clinical practices, and needs for continuing medical education: a survey of family physicians and cross-border comparison

Abstract: ObjectiveTo identify sport concussion knowledge base, practice patterns and current/preferred methods of Knowledge Transfer and Exchange (KTE) in two distinct populations of family physicians.DesignCross-sectional study, using a survey design.SettingAlberta, Canada (CAN); North/South Dakota, USA (US). Rural (64.4% US, 27.5% CAN; p=<0.001); walk-in/acute care (28.8% CAN, 12.9% US; p=0.008).ParticipantsRecruitment: CAN physicians by mail: 80/3154 responses (2.5%); US physicians: American Academy of Family Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Apart from soccer, concussion protocols are not yet widely applied in the sports of rugby union17 18 and ice hockey 19. Dissemination of new protocols into family/general practice takes time; concussion guidelines are not yet widely adopted in that setting 20. Language barriers provide additional challenges—the bulk of literature and dissemination has been in English to date.…”
Section: Implementation and Dissemination Lagmentioning
confidence: 99%
“…Apart from soccer, concussion protocols are not yet widely applied in the sports of rugby union17 18 and ice hockey 19. Dissemination of new protocols into family/general practice takes time; concussion guidelines are not yet widely adopted in that setting 20. Language barriers provide additional challenges—the bulk of literature and dissemination has been in English to date.…”
Section: Implementation and Dissemination Lagmentioning
confidence: 99%
“…[9][10] Concussion, on the other hand, is typically managed by sports medicine certified physicians, pediatricians, or athletic trainers. [10][11][12][13] Pediatric residency programs were studied in 2003 and concluded that 24% of the programs did not include formal teaching about concussions in their curriculum. 14 When family physicians and pediatricians are not available, many families will go to the emergency room for concussion visits.…”
Section: Introductionmentioning
confidence: 99%
“…An Internet-based survey of 545 family physicians in North Dakota and South Dakota revealed that 94.5% of these physicians were diagnosing and treating concussions, suggesting that, in fact, the rural setting has providers willing to manage this injury. 7 Athletic trainers, nurse practitioners, and psychologists also play a substantial role in sports concussion management, particularly on the collegiate level. Even with multiple disciplines participating in concussion treatment, it could be argued that with 1.6-3.8 million concussions per year, the lack of access to concussion care may be due to an inadequate supply of providers overall.…”
mentioning
confidence: 99%